Intravaginal administration of progesterone using a new technique for sustained drug release in goats - Natsumi ENDO; Larasati Puji RAHAYU; Takashi YAMAMURA; Hitoshi TANAKA; Tomomi TANAKA (The Society for Reproduction and Development, 2020)
The objective of the present study was to develop and evaluate a sustained release vaginal progesterone (P4) capsule containing a mixture of mucoadhesive polymer and silicone fluid. Goats were administered a gelatin capsule containing 0.4 g of P4 mixed in silicone fluid and either a hydroxypropylmethylcellulose (HM) or polyaclil starch (PA) base. The mean plasma P4 concentrations at 2 and 12 h after administration were significantly higher in goats treated with PA capsules than in those with HM capsules. The plasma P4 concentrations in goats treated with HM capsules increased and remained above 1.0 ng/ml for 96 h after administration, whereas the plasma P4 concentrations in goats treated with PA capsules remained above 1.0 ng/ml for only 24 h after administration. In the next experiment, an HM capsule was attached to a silicone device and inserted in the vagina for 10 days. The plasma P4 concentration remained similar to that of the natural luteal phase for 9 days. These results suggest that a mixture of mucoadhesive polymer and silicone fluid has the potential to be applied clinically as a sustained release base for estrus synchronization or hormonal therapy.